Phytochemical screening, antimicrobial activities and toxicity against Artemia salina Leach of extracts and fractions of Ocimum gratissimum Linn from Benin - Kpadonou-Kpoviessi, Bénédicta; KPOVIESSI, Dossou Sika Salomé; Yayi-Ladekan, Eléonore; GBAGUIDI, A. Fernand; Yehouenou, B.; MANSOUROU, Moudachirou; ACCROMBESSI, COFFI GEORGES (My University, 2013)
The antimicrobial and toxicity against Artemia salina Leach of extracts from different parts (stems, leaves and seeds) of Ocimum gratissimum collected at two vegetative stages were analyzed. In addition to essential oils that contain volatile compounds and which antimicrobial properties we studied in a previous work [12], the plant contains less or non-volatile compounds that could explain in part, its properties. The crude ethanol extract of different parts (leaves, stems and seeds in pre- and full flowering) showed yields between 1.97% and 4.81%. Leaves had given more extract than seeds and the lower yield was obtained with the stems. Antimicrobial tests and toxicity against A. salina Leach helped to identify the crude extract of leaves and stems in full flowering as the most active respectively against C. albicans ATCC, and E. coli ATCC and S. aureus ATCC with a good selectivity. Phytochemical screening of different samples revealed the presence of polyphenolic compounds (gallic and catechic tannins, flavonoids, anthocyanes and leucoanthocyanes), quinone derivatives, triterpenoids, steroids, mucilage, coumarins, reducing compounds and essential oils. The liquid-liquid fractionation of the active crude extracts with different solvents of increasing polarity showed ethyl acetate fraction as the most active. This fraction needs to be further investigated by isolation and identification of pure bioactive compounds by bio-guided fractionation. This is the first report of interaction between plant parts, vegetative stages, antimicrobial properties and toxicity of the nonvolatile fractions of O. gratissimum Linn from Benin.
Keywords: Ocimum gratissimum Linn; non-volatile fraction; antimicrobial activity; selectivity index; bio-guided fractionation.